Doing apologetics with an African mindset: equipping Africans to defend the Christian faith - Afolabi, Ebenezer (AfriCore Apologetics Publications, 2022)
In such a time as this when many churches in Africa are drifting away from biblical Christianity and adopting doctrines and practices totally foreign to the Christianity practiced by the apostles and the church fathers, it is therefore imperative to urgently engage in apologetics and polemics, so that the church in Africa can preserve and transmit the tradition of truth and biblical Christianity to the coming generations of Christians in Africa. In Doing Apologetics with an African Mindset, readers will learn the following: 1. How to do Apologetics from the African perspective, 2. The presuppositions of the dominant religions in Africa and why Christianity is unique, 3. How to engage the intellectuals and help them remove their mental barriers to the Christian faith, 4. The uniqueness of Christianity, Jesus, the Bible and the hope Christianity offer to Africans, 5. The Jesus Africans would accept and the images of Christ in Africa. This book is a valuable resource material to help missionaries, church leaders, Pastors, teachers, evangelists, seminarians, youth ministers, parents and Christian educators provide logical and biblical explanations for their Christian claims from the African perspective.
paid